'MORE' ON 'INCOME-TAX-ALLOCATION' ACCOUNTING. - Johnson, Arnold W. (The Accounting Review, 1961)
Abstract The allocation of income taxes on financial statements is a relatively new development in corporate accounting. It is an extraordinarily important development because of its significant effect upon the determination of corporate net income and because, also, it seems to represent somewhat of an erosion of certain of our long-tested and long-standing definitions and concepts as to principles of accounting. As a general rule, accounting procedures for the allocation of income taxes have resulted in the placement of certain credit values for deferred income taxes in the balance sheet. The accounts representing these credit values have been called "deferred credits." Since these accounts are not part of corporate net worth they must be liabilities. It is an accepted procedure of auditing that the revenues and revenue charges of a business must be supported by evidence, preferably written evidence. There is no billing by a creditor, no evidence of legal liability, no evidence of the erosion of the accounting value of an asset, and no evidence of the consumption of accounting value. In short, there is no factual evidence, whatsoever, to support the accounting propriety of charging current income with a provision representing deferred income taxes.